ANALISIS PERSEPSI TERHADAP BRAND AWARE DAN ATRIBUT MEREK PADA MINUMAN JUS PRODUK UKM DEPOK - Alfida, Alfida; Triwardhani, Diana; Yetti, Fitri; Alfida, Alfida (Ekonomi dan Bisnis, 2014)
This study aims to look at the perception of the public about the existence of the brand of juice Winner brand, with random sampling is done to the 167 respondents from the Depok, then given a sample product and given the questionnaires, the results obtained by descriptive is all respondents had Winner familiar juice brand, for brand association by Cochran test result is tastes good, and not bitter in throat.